Pengaruh Islamic Worldview terhadap Pendidikan Islam di PTQ Cahaya Nusantara - Rohmah, Mar-Atin Nabila; Widiyanto, Vian (TSAQOFAH, 2025)
This study aims to analyze the influence of the Islamic worldview on the Islamic education system at PTQ Cahaya Nusantara. The research is grounded in the importance of holistically internalizing Islamic values to shape students' character. A qualitative approach with a case study method was employed, and data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that educators’ understanding of the Islamic worldview is manifested in the principle of “adab before knowledge”, implemented through habituation, role modeling, and a curriculum integrated with tauhid and ethical values. Strategies include cek adab (adab checks), the integration of adab-related content into lessons, and a spiritual approach to character development. Although challenges persist, such as inconsistent behavioral transformation among students, the application of the Islamic worldview has shown a positive impact on character formation and a sense of responsibility among learners. The study concludes that integrating the Islamic worldview is a crucial element in Islamic education aimed at nurturing insan kamil through a unified approach to values, spirituality, and morality.